Investment Opportunities in BRIC Nations - A Comparative Fundamental Analysis of Indian Equity Markets - Dhingra, Gaurav (2007)
Emerging Markets like BRIC (Brazil, Russia, India and China) have attracted a lot of attention from investors all over the globe. The economies of these nations are growing at a rapid pace and these nations are expected to become a much larger force in few years from now. As a result, they have given much higher returns than the developed ones in the recent past. India with its strong fundamentals and macroeconomic stability has impressed investors worldwide and attracted enormous foreign investment. The economy is growing at a pace of 8% (in GDP terms) and its equity market has seen an unprecedented bull run. This study analyzes the opportunities in investing in these countries and finds out the advantages and disadvantages of investing in India. It also conducts a comparative analysis of investing in all above markets. The results show that there are enormous opportunities of investment in all the four nations, but India and China are expected to grow the fastest and receive larger share of investor attention and money. Indian economy seems to have a slight edge over China as it has a more diversified industry and is less exposed to global risks like a slowdown in US.